Atlas shrugged - Rand, Ayn; Herrmann, Edward 1943- (St. Paul, Minn. HighBridge, 2000)
The story takes place at an unknown time in the not-too-distant future in a fictitious United States. Focusing on the weakness of evil, corporate greed, and the parasites of society, Rand provides a compelling narrative on modern life and the death and rebirth of humanity.
Abridgement of the 1957 book.
Compact discs.
Duration: 11:30:00.
Read by Edward Herrmann.
100885
Keywords: Egoism; Capitalism; Objectivity; Didactic fiction; Audiobooks; Fiction